Early Phase of Muslim Political Movement - Jamil-ud-Din Ahmad (Lahore Publishers United Ltd., 1967)
An attempt to trace the events and causes which led the Muslims of the India - Pakistan Subcontinent to start a political movement of their own. It covers all the salient aspects of the early phase that led to Pakistan. Three volumes consist of Early Phase, Middle Phase, Final Phase.
Includes Appendix and Referenes
Keywords: Muslims -- India -- India -- Politics and Government